Meta-Analysis: The Effect of Contextual Teaching and Learning (CTL) Learning Model on Student Skills - Burhan, Hanana Laila; Asrizal, Asrizal (Journal of Innovative Physics Teaching, 2023)
This research literary study that discusses the meta-analysis that examined 17 national and international scale journals articles from 2009 to 2020. The data collection technique that will be analyzed is observation of journals based on the components of student skills. Based journals articles using the Contextual Teaching and Learning (CTL) learning model. The 17 journals articles average effect size value was 0.71 in the medium category, based on the educational level of the CTL model, the skills of students were more influential at the junior high school education level with an average effect size value of 0.952 in the large category compared to kindergarten, elementary, high school and university education levels. Based on the teaching materials used by the CTL model, students' skills are more influential in using solar system teaching materials with an average effect size value of 1.24 in the large category. As for the influence of the CTL model on student skills, the science process skills obtained are greater than critical thinking skills and creative thinking with an average effect size value of 0.816 in the large category.